A systematic literature review of the global trends of outcome-based education (OBE) in higher education with an SDG perspective related to engineering education - Mehul Mahrishi; Seeram Ramakrishna; Samira Hosseini; Asad Abbas (Discover Sustainability)
Abstract Sustainable Development Goal (SDG) 4 by the United Nations focuses on “Quality Education,” emphasizing learning outcomes and effective teaching and learning strategies. The goal is to ensure that all students achieve relevant and practical learning and that teachers have the necessary skills to provide quality education. Outcome-based education (OBE) can be one of the facilitators for promoting quality and sustainability, especially in engineering education. By providing outcome-based education, we can equip students with the skills and knowledge needed to address our world’s complex challenges and contribute to building a more sustainable and equitable society. This systematic review examines the global extent of OBE, particularly in engineering education. Research also investigates the alignment of OBE with the UN's sustainable development goals. The review is performed on the Scopus and Web of Science databases, with 49 records, using PRISMA. Scientific analysis was done with VOSviewer, which displays the results in bibliometric maps and highly responsive graphs. According to the study, the OBE framework is widely accepted internationally; however, more literature on its implementation must be published. Another issue that this review points out is the need for greater collaboration among the various active researchers working in this field, which draws an invisible boundary between the demographic implementation of OBE worldwide. The study provides in-depth evidence that OBE aligns with the SDGs of the United Nations, especially the goal of quality education. It also highlights that the limited published work on OBE hinders its implementation at all levels of university programs to produce skilled human resources to overcome the upcoming challenges. Finally, the study collects evidence helpful for LATAM nations to make possible reforms in their educational policies and implement OBE in all HEIs to promote quality education. Potentially the first of its kind, this research shows that most articles extracted from academic databases correspond precisely to the SDGs of the United Nations.